Stress, depression, and anxiety: psychological complaints across menopausal stages - Kuck, Ming Jun; Hogervorst, Eef (Frontiers in Psychiatry, 2024)
Introduction: With the number of menopausal women projected to reach 1.2 billion by 2030 worldwide, it is critically important to understand how menopause may affect women's emotional well-being and how many women are affected by this. This study aimed to explore (i) the relationship between psychological complaints (depression, anxiety, poor memory) across different menopausal stages and (ii) investigate the correlation between resilience, self-efficacy, and perceived stress levels, with psychological complaints and whether this was associated with menopausal stage and/or age.Methods: 287 respondents completed the Menopausal Quality of Life, Perceived Stress, Brief Resilience, and General Self-efficacy scales. Parametric and non-parametric analysis was used to analyse how bothered women were by self-reported poor memory and feelings of depression and anxiety, alongside perceived stress, resilience, and self-efficacy between women in different menopausal stages using STRAW criteria. The association between protective factors (self-efficacy and resilience) and psychological complaints was analysed with partial correlation analysis controlling for menopausal stages and/or age.Results: A significant difference was found between perceived stress levels, and how bothered women were by feelings of depression and anxiety between early-perimenopausal and postmenopausal women. However, with the inclusion of age as a covariate, menopausal stage no longer predicted the level of stress and anxiety. There was also no difference between poor self-reported memory, or self-efficacy or resilience between women in different menopausal stages. However, self-efficacy and resilience were associated with how bothered women were by feelings of depression and anxiety, and stress. Stress was the only variable to be associated with poor self-reported memory independent of age and/or menopausal status.Discussion: Early perimenopausal women experienced the highest level of stress and were more severely bothered by feelings of depression and anxiety, with the poorest overall psychosocial quality of life. Post-menopausal women, however, reported to have similar experiences as premenopausal women. Age explained the associations between menopausal stage, stress and anxiety, but not between depression and different menopausal stages. Resilience and self-efficacy were associated with psychological complaints independent of menopausal stage and age, suggesting that therapies focusing on increasing resilience and self-efficacy may be beneficial to help target these psychological complaints at any time.